Time to cancer treatment and reproductive outcomes after fertility preservation among adolescent and young adult women with cancer. Issue 2 (31st October 2022) - Meernik, Clare; Engel, Stephanie M.; Baggett, Christopher D.; Wardell, Ally; Zhou, Xi; Ruddy, Kathryn J.; Wantman, Ethan; Baker, Valerie L.; Luke, Barbara; Mersereau, Jennifer E.; Cai, Jianwen; Olshan, Andrew F.; et al.
Abstract: Background: Fertility preservation (FP) may be underused after cancer diagnosis because of uncertainty around delays to cancer treatment and subsequent reproductive success. Methods: Women aged 15 to 39 years diagnosed with cancer between 2004 and 2015 were identified from the North Carolina Central Cancer Registry. Use of assisted reproductive technology (ART) after cancer diagnosis between 2004 and 2018 (including FP) was assessed through linkage to the Society for Assisted Reproductive Technology. Linear regression was used to examine time to cancer treatment among women who did ( n = 95) or did not ( n = 469) use FP. Modified Poisson regression was used to estimate risk ratios (RRs) and 95% CIs for pregnancy and birth based on timing of ART initiation relative to cancer treatment ( n = 18 initiated before treatment for FP vs n = 26 initiated after treatment without FP). Results: The median time to cancer treatment was 9 to 33 days longer among women who used FP compared with women who did not, matched on clinical factors. Women who initiated ART before cancer treatment may be more likely to have a live birth given pregnancy compared with women who initiated ART after cancer treatment (age‐adjusted RR, 1.47; 95% CI, 0.98‐2.23), though this may be affected by the more frequent use of gestational carriers in the former group (47% vs 20% of transfer cycles, respectively). Conclusions: FP delayed gonadotoxic cancer treatment by up to 4.5 weeks, a delay that would not be expected to alter prognosis for many women. Further study of the use of gestational carriers in cancer populations is warranted to better understand its effect on reproductive outcomes. Abstract : In this statewide retrospective cohort, adolescent and young adult women with cancer who used fertility preservation experienced up to a 4.5‐week delay in receipt of first gonadotoxic cancer treatment, but may have an increased likelihood of live birth after achieving pregnancy compared to women with cancer who used assisted reproduction without prior fertility preservation.